2009
DOI: 10.1186/1471-2180-9-184
|View full text |Cite
|
Sign up to set email alerts
|

Identification of two GH18 chitinase family genes and their use as targets for detection of the crayfish-plague oomycete Aphanomyces astaci

Abstract: BackgroundThe oomycete Aphanomyces astaci is regarded as the causative agent of crayfish plague and represents an evident hazard for European crayfish species. Native crayfish populations infected with this pathogen suffer up to 100% mortality. The existence of multiple transmission paths necessitates the development of a reliable, robust and efficient test to detect the pathogen. Currently, A. astaci is diagnosed by a PCR-based assay that suffers from cross-reactivity to other species. We developed an alterna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 67 publications
(103 reference statements)
0
32
0
Order By: Relevance
“…The analyses conducted with MEGA, PAUP and TNT were largely congruent, with only minor differences in the statistical bootstrap support values for the different clades (data not shown). For a subset of isolates from each clade, sequences from the GH18 domains of chitinase genes generated according to Hochwimmer et al (2009) supported the ITS-based species identification (data not shown).…”
Section: Molecular Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…The analyses conducted with MEGA, PAUP and TNT were largely congruent, with only minor differences in the statistical bootstrap support values for the different clades (data not shown). For a subset of isolates from each clade, sequences from the GH18 domains of chitinase genes generated according to Hochwimmer et al (2009) supported the ITS-based species identification (data not shown).…”
Section: Molecular Characterizationmentioning
confidence: 99%
“…Parsimony analyses of the independent dataset of chitinase genes were largely congruent with the ITS phylogeny and supported 2 different genotypes of the S. diclina sub-clade IIIA and IIIB isolates. However, these data were not included due to presently unresolved problems with insufficient sequence accuracy that may relate to the simultaneous amplification and sequencing of the 3 slightly different homologues of chitinase genes CHI1, CHI2 and CHI3 (see Hochwimmer et al 2009). …”
Section: Discussionmentioning
confidence: 99%
“…The differences in PsI-genotype chitinase genes, even though evident, were minor compared to As-genotype (Makkonen et al, 2012b), which has also shown wider virulence variation in previous studies compared to what we observed with PsI-genotype in this study (Makkonen, 2013). Chitinase production has been claimed to be adaptation to parasitic life style and one of the virulence factors (Unestam, 1966;Hochwimmer et al, 2009). The reports of A. astaci adaptation to the European crayfish hosts (Jussila et al, 2011;Viljamaa-Dirks et al, 2011;Kokko et al, 2012;Svoboda et al, 2012;Kušar et al, 2013) are most probably all concerning As-genotype adaptation.…”
Section: Figurementioning
confidence: 99%
“…Oidtmann et al (2006) first established a molecular method suitable for the detection of A. astaci in American crayfish. Subsequently, DNA-based detection was employed on all three of the most important American crayfish invaders in Europe (the signal crayfish: Johnsen et al, 2007;Dunn et al, 2009;Hochwimmer et al, 2009;Skov et al, 2011; the spiny-cheek crayfish: Schulz et al, 2006;Kozubíková et al, 2006Kozubíková et al, , 2008Kozubíková et al, , 2010; and the red swamp crayfish: Aquiloni et al, 2011). The above-mentioned studies were mostly limited in geographical coverage and the number of analysed populations.…”
Section: Introductionmentioning
confidence: 99%